Copper/Persulfate-Promoted Oxidative Decarboxylative C−H Acylation of Pyrazolones with α-Oxocarboxylic Acids: Direct Access to 4-Acylpyrazolones under Mild Conditions - Tanakorn Kittikool (2019)
© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim A facile and efficient oxidative C−H acylation of N-substituted pyrazolones using α-oxocarboxylic acids as an acyl group source was developed. A combination of Cu(OAc)2 and K2S2O8 enables the reaction to proceed smoothly under air and provides a wide array of 4-acylpyrazolone products in moderate to excellent yields. The mechanism of this transformation is believed to proceed via a copper-induced decarboxylation to form the acyl-copper species. This method provides a convenient and useful route for a direct installation of an acyl moiety into bioactive pyrazolone derivatives, which can be further utilized in many applications. (Figure presented.).